Shielding Elektromagnetik Tembaga dari Proses Elektrolisis Air Limbah Industri Printed Circuit Board - Agung Yanuar Wirapraja; Handaru Bowo Cahyono; Mohamad Marhaendra Ali (Balai Besar Bahan dan Barang Teknik, 2020)
Some electronic products have high electromagnetic interference so that it gives a negative impact on the electronic devices around it. The use of electromagnetic shielding is a solution to reduce the value of electromagnetic radiation interference from electronic products. The research conducted includes the manufacture of electromagnetic shielding from copper material resulting from the electrolysis process of PCB (Printed Circuit Board) industrial wastewater and analyzing the effect of electromagnetic shielding from copper waste on the value of radiation emission. Electromagnetic shielding is made of vinyl which is coated with copper as a result of the electrolysis of PCB industrial wastewater. The measurement results show that electromagnetic shielding from copper waste can reduce radiation emissions. The use of electromagnetic shielding from copper waste is effective at frequencies from 250 to 350 MHz with a decrease in the quasi-peak value of 38.02 dB. The measurements with horizontal antenna polarization show that the margin of radiation emission value is higher comparated to vertical antenna polarization.Sebagian produk elektronika memiliki gangguan interferensi elektromagnetik yang tinggi, sehingga berdampak kurang baik terhadap perangkat elektronika di sekitarnya. Pemanfaatan shielding elektromagnetik menjadi solusi untuk mengurangi nilai gangguan radiasi elektromagnetik yang dimiliki oleh produk elektronika. Penelitian yang dilakukan meliputi pembuatan shielding elektromagnetik dari bahan tembaga hasil dari proses elektrolisis limbah industri PCB (Printed Circuit Board) dan melakukan analisa pengaruh shielding elektromagnetik dari limbah tembaga terhadap nilai emisi radiasi. Shielding elektromagnetik terbuat dari bahan vinyl yang dilapisi dengan tembaga hasil elektrolisis limbah cair industri PCB. Hasil pengukuran menunjukkan bahwa shielding elektromagnetik dari limbah tembaga dapat menurunkan emisi radiasi. Penggunaan shielding elektromagnetik dari limbah tembaga efektif di frekuensi 250 – 350 MHz dengan penurunan nilai quasi-peak sebesar 38,02 dB. Pada pengukuran dengan polarisasi antena horisontal, margin nilai emisi radiasi lebih tinggi jika dibandingkan dengan polarisasi antena vertikal. Kata Kunci: Shielding elektromagnetik, Emisi radiasi, Tembaga, PCB